New arrangements in the field of didactics: mediations, subjectivities and emerging practices (Praxis Educativa, 2023)
The field of didactics, as an object of analysis and discussion, expands from the novel mediations and modes of knowledge construction that are intertwined with emerging practices and subjectivities. This article presents the need to recognize the way in which didactic expansions in networks, platforms and devices transform the educational experience and invite to inhabit immersive processes in heterogeneous cultural fabrics. The tensions that occur in the designs that involve the amplifications of teaching practices in collective constructions are addressed and considers the approaches of multiple languages, as well as alternative times and spaces for teaching and learning. It is proposed to give rise to the possibility of recognizing new arrangements and counter-hegemonic perspectives of didactics that discuss with traditions, with the motions that are imposed with a normative claim and with the omissions that veil differences, inequalities and exclusions.
Keywords: Agency; Collective; Didactics; Design; Teaching; Mediations